Exploring the relationships between nonprofit management education and career impact: Scale development and comparison. Issue 1 (2nd January 2021) - Blau, Gary; Hill, T. L.; Cannon, Maureen
Abstract: We address the lack of scales for studying the effectiveness of nonprofit management education (NME), by using responses from 62 MBA graduates who had completed an experiential nonprofit governance course to develop six NME scales: Business Skills Enhancement; Nonprofit Skills Enhancement; Nonprofit Management Knowledge; Network Expansion; NME Application to Current Job; NME Career Impact. We explored the usefulness of these scales by examining the scales' relationship to the number of jobs and length of experience since graduation and to each other. Our findings suggest that NME-related business skills and nonprofit skills had a significant relationship to current jobs and career impact and that the number of jobs erodes NME effects.